A MUNICIPALIZAÇÃO E A INSTITUCIONALIZAÇÃO DO SISTEMA MUNICIPAL DE ENSINO EM GOIATUBA-GO (1997-2004): avanços e retrocessos do processo de democratização da educação básica pública - BUZAIM, Railda Soares (2009)
This study is situated within the research field The State and Educational Policy which is part of the Post-Graduate Program in Education of the Faculty of Education/UFG. The study analyzes the outcome of the decentralisation policies in the field of education, implanted in the country since the 1990s. It specifically investigates the process of decentralization of teaching in Goiatuba-GO, considering the profound changes in the educational reality which occurred in Goiatuba in the period between 1997 and 2004. The study sought to find out if these changes contributed to the establishment of indicators of democratization in the educational administration of the municipality analyzed. The study is constituted as a case study of the city of Goiatuba-Go. The following procedures were used to execute this research study: a) a bibliographic survey and study; b) a document research focusing on the national, state and municipal education legislation; c) the undertaking of semi-structured interviews with the principal actors of the process analyzed, that is, the mayors of the city, the municipal secretaries of education and their advisors; and d) the application of questionnaires with the school directors and pedagogic coordinators who lived through the period analyzed. The central categories of the investigation are: decentralization, municipalization, institutionalization of the educational system and democratic administration. The results of the investigation show that the process of municipalization and institutionalization of the municipal educational system in Goiatuba sought to fulfill the goals set out by the educational policies of the federal government, but were shaped by the dominant logic of local power, by party politics interference and by the non- creation of room for participation in the school administration and in the system. The process analyzed was earmarked by the relation between the public and the private domains, by the exchange of favours, which characterizes patrimonialism, by a lack of collaboration between the State and the municipality, by an absence of consultative, deliberative and supervisory bodies in the municipal schools. The municipal school system showed a lack of democratization indicators in the administration, which revealed the maintenance of clientelist and patrimonial relations, a common factor in the country and in the municipality.